Amended diagnosis of the genus Nannodiaptomus (Copepoda, Calanoida), based on redescription of N. phongnhaensis and description of a new species from caves in central Vietnam - Tran, Duc Luong; Brancelj, Anton (Zootaxa, 2017)
Nannodiaptomus phongnhaensis Dang & Ho, 2001, an endemic stygobiotic diaptomid from Vietnam and the type species of the genus Nannodiaptomus Dang & Ho, 2001, is redescribed on the basis of a new material from its type locality: Hang Phong Nha Cave, Quang Binh province, central Vietnam. We also designated a neotype, because the type material has been lost. The diagnosis of the genus is amended, based on the description of the neotype. The taxonomic position of the genus in the subfamily Speodiaptominae is proposed, and its relationships with other genera of this subfamily are discussed. A new cave-dwelling species Nannodiaptomus haii sp. nov., from a cave near the type locality of N. phongnhaensis, is also described and illustrated. The new species differs from the type species of the genus, among other things, by the structure of male’s left swimming leg 5, where the inner margin of the apical process and the sub-terminal seta on the swimming leg 5 Exp-2 have small serrated membranes, but these bear 3–4 distinct denticular protrusions in N. phongnhaensis.